Bank Risk and the Value Relevance of Fair Value Gains and Losses - LIM, Chu Yeong (Institutional Knowledge at Singapore Management University, 2011)
This paper studies the value relevance of fair value gains and losses for an international sample of banks. Logically it is possible for the increased subjectivity associated with the implementation of fair value accounting in highly risky situations to result in fair value numbers that are less value relevant. On the other hand it is logically possible that investors will find well implemented fair value estimates more useful for banks with more risky business models. Our empirical findings indicate that the first of these logical possibilities is significantly outweighed by the second. Using hand collected data we construct a bank returns model that splits the loan losses and profits before taxes of banks by the line of business (retail versus corporate). The main finding of the paper is that the value relevance of fair value gains and losses is positively related to the level of bank risk. In addition we find that the fair value gains/losses of banks that elect to use the fair value option for assets that could have been accounted for in terms of amortized costs are also more value relevant and persistent. From a policy viewpoint our results suggest that the fair value gains and losses of banks should be separately accounted for according to line of business.